1998
DOI: 10.1007/s100510050276
|View full text |Cite
|
Sign up to set email alerts
|

Stretched exponential distributions in nature and economy: “fat tails” with characteristic scales

Abstract: To account quantitatively for many reported « natural » fat tail distributions in Nature and Economy, we propose the stretched exponential family as a complement to the often used power law distributions. It has many advantages, among which to be economical with only two adjustable parameters with clear physical interpretation. Furthermore, it derives from a simple and generic mechanism in terms of multiplicative processes. We show that stretched exponentials describe very well the distributions of radio and l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
600
8
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 753 publications
(621 citation statements)
references
References 49 publications
11
600
8
2
Order By: Relevance
“…Finally, the Weibull distribution has characteristics that are similar to those of the lognormal. Laherrére and Sornette present evidence that this distribution provides excellent fits for many phenomena in nature and society [422]. However, it has so far not been used much in the context of workload modeling, perhaps because fitting the distribution's parameters is more complicated than for other candidate distributions.…”
Section: The Lognormal and Other Candidate Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the Weibull distribution has characteristics that are similar to those of the lognormal. Laherrére and Sornette present evidence that this distribution provides excellent fits for many phenomena in nature and society [422]. However, it has so far not been used much in the context of workload modeling, perhaps because fitting the distribution's parameters is more complicated than for other candidate distributions.…”
Section: The Lognormal and Other Candidate Distributionsmentioning
confidence: 99%
“…Similar models can also lead to a Weibull distribution [269,422]. Moreover, the differences between the models may be small in practical situations.…”
Section: Model Selection and Sensitivity To Detailsmentioning
confidence: 99%
“…It turns out that the observed rank-frequency dependencies are much better approximated by one of the alternatives to the power-law (2), namely the stretched exponential distribution. This type of distribution is used to describe large variety of phenomena from physics to finance [17]. It was observed, e.g., for rank distributions of radio/light emission intensities from galaxies, French and US agglomeration sizes, daily Forex US-Mark price variation, etc.…”
Section: Statistical Properties Of the Wiki And Np Tagsmentioning
confidence: 99%
“…ponential distribution as done by Laherrere and Sornette [31]. However, the stretched exponential distribution is not suitable for the citation index of Brazilian physicists.…”
Section: Figmentioning
confidence: 99%
“…Laherrere and Sornette [31] presented numerical evidence, on the basis of data for the 1120 most cited physicists from 1981 to June 1997, that the citation distribution of individual authors is associated with a stretched exponential form, N(x) ∼ exp − (x/x 0 ) β , with β 0.3. Using the technique of the Zipf plots, Redner [32] has recently shown that the distribution of citations of the most cited scientific papers is described by a power law, N(x) ∼ x −α , with α 3.0.…”
Section: Introductionmentioning
confidence: 99%